2017
DOI: 10.1017/s0954579417001274
|View full text |Cite
|
Sign up to set email alerts
|

Stress exposure and psychopathology alter methylation of the serotonin receptor 2A (HTR2A) gene in preschoolers

Abstract: Serotonin signaling pathways play a key role in brain development, stress reactivity, and mental health. Epigenetic alterations in the serotonin system may underlie the effect of early life stress on psychopathology. The current study examined methylation of the serotonin receptor gene HTR2A in a sample of 228 children including 119 with child welfare documentation of moderate to severe maltreatment within the last 6 months. Child protection records, semi-structured interviews in the home, and parent reports w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 61 publications
0
25
0
1
Order By: Relevance
“…Interestingly, 5HT1A is also the target of miR-16, which has its expression modulated by ELS (Bai et al, 2012). The receptor 5HT2A is, as well, modulated by ELS in animals and humans (Rentesi et al, 2013;Parade et al, 2017) and involved with the pathophysiology of obesity (Rosmond et al, 2002;Huang et al, 2004). Interestingly, the 5HT2A is also targeted by the miR-16 (Yang et al, 2017).…”
Section: Perspectives: Role Of the Mirnas On The Onset Of Obesity Thrmentioning
confidence: 99%
“…Interestingly, 5HT1A is also the target of miR-16, which has its expression modulated by ELS (Bai et al, 2012). The receptor 5HT2A is, as well, modulated by ELS in animals and humans (Rentesi et al, 2013;Parade et al, 2017) and involved with the pathophysiology of obesity (Rosmond et al, 2002;Huang et al, 2004). Interestingly, the 5HT2A is also targeted by the miR-16 (Yang et al, 2017).…”
Section: Perspectives: Role Of the Mirnas On The Onset Of Obesity Thrmentioning
confidence: 99%
“…Hypothesis and mechanism-focused candidate gene studies have identified PTSD-related differences in DNAm levels in genes associated with the hypothalamicpituitary-adrenal (HPA) axis (e.g., ADCYAP1 [9], FKBP5 [10], and NR3C1 [11]), inflammation (e.g., BDNF [4], HTR2A [12] and IL-18 [13]), and neurotransmission (e.g., BDNF [4], HTR2A [14], and HTR3A [15]). Epigenome-wide association studies (EWASs), on the other hand, take a hypothesis-free approach to identifying DNAm loci from across the genome that are statistically associated with the phenotype of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigating temporal changes of DNA methylation in adult blood found dynamic changes of DNA methylation of stress-associated genes within 30 minutes of acute psychosocial stress [47]. More recently, there has been growing interest in identifying dynamic changes in DNA methylation that occur early in life [11][12][13]48].…”
Section: Pcr and Specific Analysismentioning
confidence: 99%
“…It is non-invasive, does not require specialized equipment or training and can be stored at room temperature for more than a year, making it feasible to sample outside of a laboratory. When compared to a blood draw, saliva is also more easily collected from young children [11][12][13][14]. Finally, it is convenient for repetitive collection from the same participant, making saliva a useful proxy tissue for epidemiological studies such as birth cohorts [15,16].…”
Section: Introductionmentioning
confidence: 99%